Small-Signal Stability Analysis of Power Systems Integrated with Variable Speed Wind Generators - Du, Wenjuan (Springer International Publishing, 2018)
This book reviews and examines how power system low-frequency power oscillations and sub-synchronous oscillations may be affected by grid connection of wind power generation. Grid connection of wind power generation affects the power system small-signal stability and has been one of the most actively pursued research subjects in power systems and power electronics engineering in the last ten years. This book is the first of its kind to cover the impact of wind power generation on power system low-frequency oscillations and sub-synchronous oscillations. It begins with a comprehensive overview of the subject and progresses to modeling of power systems and introduces the application of conventional methods, including damping torque analysis, modal analysis and frequency-domain analysis, presented with detailed examples, making it useful for researchers and engineers worldwide.